Complexity-Aware Monitoring Discussion Note (Screencast) - Patsalides, Melissa; Britt, Heather (2014)
This screencast covers information included in the Complexity-Aware Mo nitoring Discussion Note. The topic is intended for those seeking cutt ing-edge solutions to monitoring complex aspects of strategies and pro jects. Most of the principles and promising approaches discussed here have a significant body of theory and practice behind them, but many h ave not been used to monitor USAID strategies and projects. We have mu ch to learn about whether and how they can be applied successfully in the Agency. USAID's Office of Learning, Evaluation, and Research in th e Bureau of Policy, Planning, and Learning has partnered with differen t groups through monitoring trials to build a body of evidence regardi ng which complexity-aware M&E approaches are most effective in the con texts of USAID programming.